Metal-organic framework nanosheets: Preparation and applications - Li, Yan-zhou; Fu, Zhi-hua; Xu, Gang (Coordination chemistry reviews, 2019)
•This paper reviewed the recent research progress on MOF nanosheets.•Almost all MOF nanosheets prepared in last decade under different synthetic strategies were summarized.•Key application of MOF nanosheets are listed.•The challenges and outlooks on MOF nanosheets are specifically outlined. Metal-organic framework (MOF) nanosheets have attracted extensive attention due to their remarkable properties, such as nanoscale and tunable thickness, adjustable structure and function, high-aspect-ratio, large surface area, more exposed accessible active site, favorable mechanical flexibility, and optical transparency. This article aims to review the latest developments in MOF nanosheets. Firstly, the assortments of the synthetic methods of MOF nanosheets will be introduced. Then, the wide applications and utilization of these ultrathin MOF nanosheets in the fields of electronics, gas separation, catalysis, sensors, energy storage/transfer, and as enzyme inhibitors will also be explored. Finally, the prospects and challenges of MOF nanosheets will be presented.